The Pivotal Factors of Housing Satisfaction in Public Rental Housing: A Literature Review - Yasfindo, Agrie; Adianto, Joko (International Journal of Built Environment and Scientific Research, 2025)
This study examines the factors that influence housing satisfaction in public rental housing, which frequently encounters challenges such as less-than-ideal neighborhoods and constrained resident autonomy. Housing satisfaction can be defined as the congruence between the expectations of residents and the conditions in which they live. A literature review was conducted to identify the main categories of satisfaction determinants. These were found to be socio-demographic, environmental, and physical. Socio-demographic factors encompass age, gender, marital status, education, occupation, household type, economic status, and duration of residence. Environmental factors encompass accessibility, physical quality, cleanliness, safety, and social relationships. In addition, the physical aspects of housing satisfaction encompass the design of the building, the configuration of the interior space, and the quality of the materials and construction. The results demonstrate that the interplay between these three factors is instrumental in fostering a comfortable, secure, and conducive housing experience for residents, which is crucial for the successful advancement of public rental housing.